2020
DOI: 10.1021/acsnano.0c00506
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Magnetic Tuning of Optical Properties of Films of Cholesteric Cellulose Nanocrystals

Abstract: Chiral photonic crystals derived from the self-assembly of cellulose nanocrystals (CNCs) have found important applications in optical devices due to the capacity to adjust the chiral nematic phase under external stimulus, in particular an applied magnetic field. To date, strong magnetic fields have been required to induce an optical response in CNC films. In this work, the self-assembly of films of CNCs can be tuned by applying an ultrasmall magnetic field. The CNCs, decorated with Fe3O4 nanoparticles (Fe3O4/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 46 publications
0
50
0
Order By: Relevance
“…If the pitch matches the wavelength of visible light, then the lms can appear iridescent. Interesting materials have been developed based on the liquid crystalline nature of CNCs, including lms, 8,9 microcapsules, 10 3D printer inks, 11 hydrogels, 12,13 aerogels, 14 and hybrid composites. 15,16 The chiral nematic structure of CNCs has also been used as a template to form other chiral nematic materials such as chiral nematic silicate glasses.…”
Section: Introductionmentioning
confidence: 99%
“…If the pitch matches the wavelength of visible light, then the lms can appear iridescent. Interesting materials have been developed based on the liquid crystalline nature of CNCs, including lms, 8,9 microcapsules, 10 3D printer inks, 11 hydrogels, 12,13 aerogels, 14 and hybrid composites. 15,16 The chiral nematic structure of CNCs has also been used as a template to form other chiral nematic materials such as chiral nematic silicate glasses.…”
Section: Introductionmentioning
confidence: 99%
“… 31 , 32 The reflected colors can be substantially altered and red-shifted using polymers to “stretch” the helices into larger structures 32 35 or nanoparticles interacting with external fields. 36 The theory formulated by De Vries 37 allows for associating the optical rotation with the pitch of the CNC helix ( eq 1 ) where λ is the reflected light wavelength normal to the CNC film plane, n is the average refractive index of the film, P is the pitch size, and θ is the angle of incidence to the plane.…”
Section: Introductionmentioning
confidence: 99%
“…When the helix axis m is along the -axis, the director n will be rotated to the left by a certain angle layer-bylayer, which makes the whole structure spiral (Werbowyj and Gray 1984;Schütz et al 2020). When director n is rotated 360 degrees, the distance between the layers is called the helical pitch (Fleming et al 2001;Pan et al 2010), often referred to as P. Generally, the P value ranges from a hundred nanometers to several micrometers and is controlled mainly by the nanocrystal concentration, geometry, electrostatic charge and external conditions such as magnetic field, polymer and so on (Hiraia et al 2009;Pan et al 2010;Espinosa et al 2013;Chen et al 2020;Bardet et al 2014).…”
Section: Theoretical Structure and Optical Properties Of Cnc-based Liquid Crystalsmentioning
confidence: 99%
“…That was helpful for designing and controlling optical properties of CNC-based LC film. Chen et al (2020) added Fe3O4 nanoparticles into CNC solution and adjusted the value of P by applying an ultra-small magnetic field. Research showed that with the increase of magnetic field strength, the P of CNC-based LC film decreases.…”
Section: Controlled Film Of Cnc-based Liquid Crystalsmentioning
confidence: 99%